منهج القياس في فقه مختلف الحديث عند ابن قتيبة الدينوري - abdul malik ghozali (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2016)
AbstractProphet Tradition (hadith) is the second main source in Islam. Unlike Koran that has completely validated as revelation, meanwhile hadith must be examined its validation of trasmission and matan. Therefore, problematic hadith  appeared, in transmission or matan. Especially, the problematic hadith in wich its matan contradicted, that called ‘musykil al-hadits’ or ‘mukhtalaf al-hadits’. Mukhtalaf al-Hadith, appearly, its matan contradicted with Koran, other equal hadith, axioma or reality. So, Mukhtalaf al-Hadits  is more debatable. Mu’tazila who representative of Rasionalits, rejected existence of mukhtalaf al-hadits as source of religion. Otherwise, Tradisionist (Ahl Hadīts) accepted it as source of religion, when its transmission comfirmed/validated. To realease contradiction of mukhtalaf hadits matan, Ibnu Qutayba, one of Muhaddits used  many rational methods; analogy (qiyās ushūlī) and syllogism (qiyās manthiqī). This research used content analysis with some approaches; Jurisprudence, Logic, Ushul Fiqh.